2007
DOI: 10.1111/j.1460-9592.2006.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of small‐dose fentanyl and sufentanil blunting the cardiovascular responses to laryngoscopy and intubation in children

Abstract: When used as part of anesthesia induction with propofol in children, sufentanil 0.2 microg x kg(-1) 2 min before induction is more effective in attenuating the cardiovascular intubation response than fentanyl 2 microg x kg(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Our results are different from the one reported in the studies of Mireskandari et al (6), Ko et al (27) and Xue et al (26) studies. Our study has been focused on the hemodynamic changes following the intubation of traumatic patients with ASA classification I and II who have normal blood pressure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are different from the one reported in the studies of Mireskandari et al (6), Ko et al (27) and Xue et al (26) studies. Our study has been focused on the hemodynamic changes following the intubation of traumatic patients with ASA classification I and II who have normal blood pressure.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, various doses of the same medication were administered. In contrast, different agents were used in our study (26). Ko et al in their study on 90 patients with age greater than 65 years old, have concluded that pretreatment with remifentanil, rather than fentanyl, is more effective in suppressing cardiovascular responses due to endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Moreover, when used as part of anesthesia induction with propofol in children, sufentanil 0.2 μg/kg 2 min before induction was effective in attenuating the cardiovascular intubation response. [30]…”
Section: Discussionmentioning
confidence: 99%
“…The timing of endotracheal intubation was decided by the anesthesiologist who was blinded to the study protocol and the MDoloris monitoring system. The research team was responsible for recording the NIPE, HR and MBP measurements immediately before and 1 min after tracheal intubation and skin incision [20]. The changes in the MBP and HR during the observation were calculated by the following formula:…”
Section: Methodsmentioning
confidence: 99%